2022
DOI: 10.1111/head.14295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the clinical utility of the patient‐identified most bothersome symptom measure from PROMISE‐2 for research in migraine prevention

Abstract: Objective: To assess the utility of the novel patient-identified (PI) most bothersome symptom (MBS) measure from PROMISE-2, a phase 3 trial of eptinezumab for the preventive treatment of chronic migraine. Background: Relief of bothersome migraine symptoms can influence satisfaction with treatment and therapeutic persistence. Understanding the impact of preventive treatment on a PI-MBS could improve clinical decision-making. Methods: In PROMISE-2, patients with chronic migraine received eptinezumab 100, 300 mg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For the PI-MBS [30,31], patients verbally described the most bothersome symptom that they associated with their migraine at the baseline visit. The investigator then categorized the verbal response into predefined categories including nausea, vomiting, sensitivity to light, sensitivity to sound, mental cloudiness, fatigue, pain with activity and mood changes, with an "other" category available with free-text description at the investigator's discretion.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…For the PI-MBS [30,31], patients verbally described the most bothersome symptom that they associated with their migraine at the baseline visit. The investigator then categorized the verbal response into predefined categories including nausea, vomiting, sensitivity to light, sensitivity to sound, mental cloudiness, fatigue, pain with activity and mood changes, with an "other" category available with free-text description at the investigator's discretion.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%
“…39,40 PI-MBS improvement was found to be significantly correlated with improvement in other patient-reported outcomes. 40 Patients were asked to verbally identify their most bothersome symptom associated with headache (nausea, vomiting, photophobia, phonophobia, pain with activity, mental cloudiness, fatigue, mood changes, or other) at the baseline visit. At Months 3 and 6, patients were asked to rate the change in their MBS since the last visit on a 7-point scale ("very much improved" to "very much worse").…”
Section: Study Assessmentsmentioning
confidence: 86%
“…Previous literature has shown that photophobia is the most commonly endorsed symptom, especially when patients are asked to select from the three standard MBS options [ 23 ]. However, in a previous study in which patients with chronic migraine self-identified their MBS, patients reported 23 unique symptoms, of which the most common were light sensitivity, nausea/vomiting, and pain with activity [ 22 ]. The MBS may be different for individual patients and may change over time.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of acute migraine treatment evaluate an MBS using an investigator-led questionnaire about the incidence of 3 common symptoms. In more recent studies, a patient-identified MBS measurement has been used [ 22 , 23 ]. In the Migraine Report Card survey, we offered respondents an expanded list of symptoms from which to identify the most bothersome, including headache pain, photophobia, phonophobia, nausea, and cognitive impacts, among others.…”
Section: Introductionmentioning
confidence: 99%